Association of risk factors and breast cancer among women treated at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: a case–control study. Issue 9 (22nd September 2022) - Hassen, Fatuma; Enquselassie, Fikre; Ali, Ahmed; Addissie, Adamu; Taye, Girma; Tsegaye, Aster; Assefa, Mathewos
Abstract : Objectives: Many factors known to increase the risk of breast cancer, such as age, family history, early menarche and late menopause are not modifiable. Modifiable factors include obesity, use of menopausal hormones and breast feeding. This study aimed to assess risk factors associated with breast cancer among women at Tikur Anbessa Specialized Hospital. Design: Facility based case–control study. Methods: Case–control study was conducted from May 2018 to June 2019. A total of 230 cases and 230 controls participated in the study. Data were analysed using SPSS software. Multivariable logistic model based analysis was conducted to control the effect of potential confounding factors. ORs and 95% CI for the likelihood of developing breast cancer were calculated. Results: The odds of breast cancer was higher among women between 40 and 49 years (adjusted OR (AOR): 3.29, 95% CI 1.39 to 7.77), and being unemployed (AOR: 4.28, 95% CI 2.00 to 9.16). Regarding life style risk factors, women consuming solid oil and using wood or animal dung as source of fuel had significantly higher odds of breast cancer. In addition, the odds of breast cancer was significantly higher among postmenopausal women, women who had previous benign surgery and women with early menarche (<12 years). On the other hand, the odd of breast cancer was significantly lower among women who had moderate physical activities. Conclusion: This study showed that occupational status, consumption of solid oil, and using wood or animal dung as source of fuel, early menarche, menopausal status and previous benign breast surgery were associated with breast cancer. On the other hand, physical activity was protective factor. Therefore, there is a need to design appropriate intervention to educate women about life style change or behaviour modification to decrease their breast cancer risk.